Actigraphy‐assessed sleep during school and vacation periods: a naturalistic study of restricted and extended sleep opportunities in adolescents. (2nd September 2013) - Bei, Bei; Allen, Nicholas B.; Nicholas, Christian L.; Dudgeon, Paul; Murray, Greg; Trinder, John
Summary School‐related sleep restriction in adolescents has been identified by studies comparing weekday and weekend sleep. This study compared weekday and vacation sleep to assess restricted and extended sleep opportunities. One‐hundred and forty‐six adolescents (47.3% male) aged 16.2 ± 1.0 years (M ± SD) from the general community wore an actigraph continuously for 4 weeks: the last week of a school term (Time‐E), the following 2‐week vacation, and the first week of the next term. Self‐reported sleep was assessed for each of the three time intervals, and chronotype was assessed using the Morningness–Eveningness Questionnaire at Time‐E. Daily actigraphy bedtime, rise‐time, time‐in‐bed, total sleep time, sleep onset latency, sleep efficiency, and % wake after sleep onset were analysed using latent growth curve modelling. The removal of school‐related sleep restriction was associated with an abrupt delay in sleep timing and increase in sleep duration. Subsequently, bedtime and rise‐time showed further linear delays throughout the vacation, while changes in time‐in‐bed were non‐significant. Sleep onset latency increased linearly, peaking in the middle of the second vacation week. Across the first vacation week, total sleep time and sleep efficiency linearly decreased, while % wake after sleep onset increased. These changes stabilized during the second vacation week. Older age and eveningness were associated with later bedtime and rise‐time, whilst females had longer time‐in‐bed, total sleep time and sleep onset latency. Compared with school days, sleep during the vacation was characterized by later timing, longer duration, lower quality and greater variability. Recovery from school‐related sleep restriction appeared to be completed within the 2 weeks of naturalistic extended sleep.